(untitled) (RUNA, archivo para las ciencias del hombre, 2012)
Hernández Aracena, Roberto y Pezo Orellana, Luis (eds). La Ruralidad Chilena Actual; Aproximaciones desde la Antropología. Santiago de Chile, CoLibris, 2010. ISBN 978-956-8993-00-9, pp. 388.